Implementasi Algoritma Promethee Dalam Melakukan Analisa Performa Matauang Virtual - Karim, Ahmad; Diansyah, T.M; Liza, Rizko (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2022)
Over the last few years, digital currencies have been rapidly gaining public attention: When cryptocurrencies are created, all confirmed transactions are stored in a general ledger. All coin owner identities are encrypted to ensure the validity of the listing. Because the currency is decentralized, when the owner owns the digital coin Neither the government nor the bank has control over it. The number of performance (criteria) of each virtual currency certainly requires an appropriate method to accommodate these criteria. Virtual currency performance analysis can be used as an answer to this problem. Analysis of the performance of virtual currencies is useful for getting the best investment commodities. Performances (criteria) that can be used as a benchmark for the success of a virtual currency as an investment commodity include the price per coin, Market Capitalization, the number of twitter followers, google trends, coin price increases, the number of coins that have been traded (circulating). supply) and the total number of coins available (max supply). The result of this research is an analysis of virtual currency performance with the promethea algorithm. The purpose of this study is to analyze the level of investment need for people who want to do business in the cryptocurrency field and produce a multi-criteria preference index analysis using Promethee. Keywords: Cryptocurrency, virtual money, algorithm